Chelated minerals and two limestone particle sizes on production of layers in the second laying cycle - SOUSA,Alisson Melo de (2017)
SUMMARY The aim of this experiment was to evaluate the performance, egg quality, and bone quality of commercial white-egg layer hens in the second production cycle fed diets containing organic and inorganic minerals and two limestone particle sizes. A total of 215 birds with an average weight of 1.527 ± 0.092 kg were distributed in a completely randomized design in a 2 × 2 factorial arrangement (two mineral sources and two limestone particle sizes) with six replicates. The following four treatments were tested: T1 = inorganic minerals + 100% fine limestone; T2 = inorganic minerals + 50% fine limestone + 50% coarse limestone; T3 = organic minerals + 100% fine limestone; and T4 = organic minerals+ 50% fine limestone + 50% coarse limestone. No significant interaction occurred between the studied factors for any variable. Egg production, egg mass, bone resistance and bone deformity were higher with organic supplementation. Eggshell weight, percentage of eggshell, and specific gravity were higher in the treatments with the fine+coarse limestone association. In conclusion, organic mineral supplementation improves the performance based on egg production and egg mass. The association between fine and larger-sized limestone improves the external quality of eggs. The use of organic minerals improves the bone quality of birds in the second production cycle.